Taxonomy of compulsory and incentive legal consequences (legal measures) of committing illegal acts - Козаченко, Олександр Васильович; Козаченко, О. В.; Козаченко, Александр Васильевич; Kozachenko, Oleksandr V.; Василяка, Олеся Костянтинівна; Василяка, О. К.; Василяка, Олеся Константиновна; Vasyliaka, Olesia K.; Чорнозуб, Лариса Василівна; Чорнозуб, Л. В.; Чорнозуб, Лариса Васильевна; Chornozub, Larysa V.; et al. (Universidad del Zulia Maracaibo : Venezuela, 2020)
The article is prepared for the purpose of publishing the results of scientific research obtained in the process of applying the taxonomic methodology for systematization of measures of legal influence. The methodology used the approaches of philosophical and legal theorization, a dog and systemic functional. One way of conclusion is proposed for the first time to use the taxonomies of legal measures. The study highlighted three aspects of legal measures: relational, predicate and functional. The relational manifestation of taxonomy allowed to identify the substrate of the external form of legal influence, which is the measure. It has been established that the form and method of legal influence is the dominant element of each legal measure. The predicative dimension of taxonomy allowed to form a taxonomic system of information in which the following taxonomic categories and taxa are distinguished: type - social events; subtype - legal measures; class - public and private legal measures; gender - separation of legal measures according to their sectoral affiliation; subgenre: the allocation of incentives and coercive measures; supervision - legal measures in their various forms and other measures that have no signs of legal liability.

Стаття підготовлена ​​з метою опублікування результатів наукових досліджень, отриманих у процесі застосування таксономічної методології для систематизації заходів правового впливу. Методологія використовувала підходи філософсько-правової теорії, контрольний та системний функціонал. Один із висновків - пропонується вперше використовувати таксономії правових заходів. Дослідження висвітлило три аспекти правових заходів: реляційний, предикатний та функціональний. Реляційний прояв таксономії дозволив виявити субстрат зовнішньої форми правового впливу, який є мірою. Встановлено, що форма та метод правового впливу є домінуючим елементом кожного правового заходу. Предикативний вимір таксономії дозволив сформувати таксономічну систему інформації, в якій виділяють такі таксономічні категорії та таксони: тип - соціальні події; підвид - правові заходи; клас - публічні та приватні правові заходи; род - поділ правових заходів відповідно до їх галузевої належності; піджанр: розподіл стимулів та примусових заходів; нагляд - правові заходи у різних їх формах та інші заходи, що не мають ознак юридичної відповідальності.

Статья подготовлена ​​с целью опубликования результатов научных исследований, полученных в процессе применения таксономической методологии для систематизации мер правового воздействия. Методология использовала подходы философско-правовой теории, контрольный и системный функционал. Один из выводов - предлагается впервые использовать таксономии правовых мер. Исследование осветило три аспекта правовых мер: реляционный, предикатный и функциональный. Реляционное проявление таксономии позволило выявить субстрат внешней формы правового воздействия, который является мерой. Установлено, что форма и метод правового воздействия является доминирующим элементом каждого правового мероприятия. Предикативное измерение таксономии позволило сформировать таксономическую систему информации, в которой выделяют такие ранги и таксоны: тип - социальные события; подвид - правовые меры; класс - публичные и частные правовые меры; род - разделение правовых мер в соответствии с их отраслевой принадлежностью; поджанр: распределение стимулов и принудительных мер; надзор - правовые меры в различных их формах и другие мероприятия, не имеющие признаков юридической ответственности.
Kozachenko O. V. Taxonomy of compulsory and incentive legal consequences (legal measures) of committing illegal acts / O. V. Kozachenko, О. К. Vasyliaka, L. V. Chornozub, О. М. Musychenko // Cuestiones Políticas. – Special Issue, V. 38. – Universidad del Zulia Maracaibo : Venezuela, 2020. – P. 151-168.
Keywords: taxonomy; substrate of the legal measure; taxon taxonomic categories (ranges); classification of legal measures; alternative legal studies; таксономія; субстрат правового заходу; таксономічні категорії таксонів (діапазони); класифікація правових заходів; альтернативні юридичні дослідження; таксономия; субстрат правовых мер; таксономические категории (диапазоны) таксона; классификация правовых мер; альтернативные юридические исследования; Research Subject Categories::LAW/JURISPRUDENCE